Respuesta :
Answer:
The value of given expression is 9.
Step-by-step explanation:
The given expression is
[tex]12-(-21)[/tex]
According to the rule of addition and subtraction,
[tex](-)\cdot (-)=(+)[/tex]
It means,
[tex]a-(-b)=a+b[/tex]
By using above rule we get,
[tex]12-(-21)=-12+21[/tex]
[tex]12-(-21)=9[/tex]
Therefore the value of given expression is 9.
Answer:
the answer of this expression is 9.
Step-by-step explanation:
we have given expression
- 12 -( - 21)
we have to find the difference
according to the addition and subtraction rule:
( - ) . ( - ) = (+)
this means
a -( - b ) = a + b
we use above rule to find the difference of - 12 - ( - 21 ).
- 12 - ( - 21 ) = - 12 + 21
- 12 + 21 = 9
9 is the required answer .